EFEKTIVITAS EM-4 DALAM MENURUNKAN KADAR COD LIMBAH CAIR BATIK CAP DI KELURAHAN SIMBANG WETAN KABUPATEN PEKALONGAN JAWA TENGAH - Wintah, Wintah; Kiswanto, Kiswanto; Sulistiyowati, Endah (JURNAL LITBANG KOTA PEKALONGAN, 2020)
The objectives of this research are: (1) To know the effectiveness of lowering the rate of liquid waste COD stamp batik. (2) To know the most effective dose of the EM-4 in lowering the COD levels of liquid waste of stamp batik. (3) To know the day of how many EM -4 is most effective in lowering COD's liquid waste stamp batik. The study used the complete random design of the factorial pattern of dosage EM-4 0 ml/L, 10 ml/L, 15 ml/L and prolonged incubation for 1 day, 2 days, 3 days. The Data obtained is analyzed using two-lane analysis (Two Way Anova). Based on the results of the analysis of the treatment EM-4 and the old incubation against the liquid waste stamp batikobtained the following results: At a group of doses acquired F count = 4209.382 > F table 5% = 3.55, then H0 rejected or there is a real influence of various doses of EM -4 which is used against COD levels. At the time group gained F count = 77.756 > F table 5% = 3.55, then concluded that there is a real influence of incubation time against the rate of COD waste car stamp batik. The most effective EM-4 dosage to lower COD levels of liquid waste stamp batikis 15 ml/l which is capable of lowering COD levels by 96.24% and the most effective prolongedincubation time is the first day. Keywords: Effectiveness, Prolonged incubation, EM-4, COD, Waste batik stamp.